Inhalable microplastics prevails in air: Exploring the size detection limit. (April 2022) - Xie, Yichun; Li, Yan; Feng, Yan; Cheng, Wei; Wang, Yan
Graphical abstract: Abstract: Microplastics (MPs) are ubiquitous in the environment, including the atmosphere. Yet, the size detection limit in measuring airborne MPs undermines the determination of the human MP exposure level through inhalation and also restricts the understanding of airborne MPs pollution behavior. To comprehensively and accurately assess the MPs pollution features in air, we demonstrate a qualitative and quantitively method using Raman microscopy to characterize the suspended atmospheric MPs. Our methodology has achieved detailed characterization of MPs down to 1 μm and ensured all the MPs to be counted regardless of their transparency. Further, a case study of indoor and outdoor samples from eight sampling sites were conducted in Shanghai, China. Inhalable MPs prevails in all samples with higher concentrations occur indoors. Indoor MPs varied strongly in composition compare to outdoor. Ventilation played an important role in lowering indoor MPs concentrations, and MPs in better ventilated indoors displayed similar distribution patterns as outdoors. MPs detected were mainly Polyethylene, Polyester, Phenolic Resin and Polyvinyl chloride. 77% of the Polyethylene detected were transparent films, suggesting the fragmentation from PE film products, such as plastic bags and cling films. Our work confirmed the widespread existences of inhalable MPs in air and provides solid foundations for future studies to understand the realistic MPs exposure conditions through inhalation.